Association between maternal parity status and premature rupture of membranes among delivering mothers - Efi Trimuryani; Asri Novia Rahmawati (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: Premature rupture of membranes (PROM) is one of the major obstetric complications associated with maternal and neonatal morbidity, particularly preterm birth. Maternal parity has been identified as one of the obstetric factors that may influence the occurrence of PROM; however, evidence regarding this association remains inconsistent. Purpose: To determine the association between maternal parity and the incidence of premature rupture of membranes among delivering mothers. Method: A retrospective analytic study with a cross-sectional design was conducted using secondary data from medical records at Panembahan Senopati Bantul Regional Hospital, Yogyakarta. The study population consisted of 168 mothers diagnosed with PROM, and 63 eligible participants were selected based on the inclusion and exclusion criteria. Maternal parity was categorized as primiparous and multiparous. Data were analyzed using the Fisher's Exact test with a significance level of p<0.05. Among 63 mothers with PROM, 81.0% experienced term PROM, while 19.0% had preterm PROM. Most respondents were aged 20–35 years (69.8%) and were multiparous (61.9%). Statistical analysis demonstrated a significant association between maternal parity and the incidence of PROM (p=0.044). Primiparous mothers had a 4.38-fold higher likelihood of experiencing PROM compared with multiparous mothers (OR=4.38). Conclusion: Maternal parity was significantly associated with the incidence of premature rupture of membranes. Primiparous mothers were at greater risk of experiencing PROM than multiparous mothers. Early identification of parity-related risk factors during antenatal care may contribute to the prevention of PROM and improve maternal and neonatal outcomes.